A bioinformatic analysis of T-cell epitope diversity in SARS-CoV-2 variants: association with COVID-19 clinical severity in the United States population - Kim, Grace J.; Elnaggar, Jacob H.; Varnado, Mallory; Feehan, Amy K.; Tauzier, Darlene; Rose, Rebecca; Lamers, Susanna L.; Sevalia, Maya; Nicholas, Najah; Gravois, Elizabeth; Fort, Daniel; Crabtree, Judy S.; et al. (Frontiers in Immunology, 2024)
Long term immunity against SARS-CoV-2 requires identification of T cell epitopes affecting host immunogenicity. In this computational study, we explored the CD8+ epitope diversity estimated in 27 of the most common HLA-A and -B alleles, representing most of the United States population. Analysis of 16 SARS-CoV-2 variants (B.1, Alpha (B.1.1.7), 5 Delta (AY.100, AY.25, AY.3, AY.3.1, AY.44), and 9 Omicron (BA.1, BA.1.1, BA.2, BA.4, BA.5, BQ.1, BQ.1.1, XBB.1, XBB.1.5)) in analyzed MHC Class I alleles revealed SARS-CoV-2 CD8+ epitope conservation was estimated at 87.6-96.5% in spike (S), 92.5-99.6% in membrane (M), and 94.6-99% for nucleocapsid (N). As the virus mutated, an increasing proportion of S epitopes experienced reduced predicted binding affinity: 70% of Omicron BQ.1- XBB.1.5 S epitopes experienced decreased predicted binding, as compared to ~ 3% and ~15% in earlier strains Delta AY.100-AY.44 and Omicron BA.1-BA.5, respectively. Additionally, we identified several novel candidate HLA alleles that may be more susceptible to severe disease, notably HLA-A*32:01, -A*26:01, and -B*53:01, and relatively protected from disease, such as -A*31:01, -B*40:01, -B*44:03, and -B*57:01. Our findings support the hypothesis that viral genetic variation affecting CD8 T-cell epitope immunogenicity contributes to determining the clinical severity of acute COVID-19. Achieving long term COVID-19 immunity will require understanding the relationship between T cells, SARS-CoV-2 variants, and host MHC Class I genetics. This project is one of the first to explore the SARS-CoV-2 CD8+ epitope diversity that putatively impacts much of the United States population.